2010
DOI: 10.1097/mpg.0b013e3181d1b107
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Oesophagitis in Infants and Children in the Region of Southern Denmark: A Prospective Study of Prevalence and Clinical Presentation

Abstract: We report a European prospective study of EE. It was documented in 6 of 78 patients with symptoms of GERD corresponding to an annual incidence of 0.16/10,000 infants and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 13 publications
3
52
1
7
Order By: Relevance
“…The majority of the patients being white, which reflects the patient population in the area, is in concordance with the current literature showing that EoE disproportionally affects non-Hispanic white subjects. 1,7,11 In accordance with the literature, our findings illustrate a high prevalence of comorbid atopic diseases and sensitizations to food and environmental allergens in both children and adults. However, we found that children had a significantly higher rate of asthma and positive patch test to foods compared with adults.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The majority of the patients being white, which reflects the patient population in the area, is in concordance with the current literature showing that EoE disproportionally affects non-Hispanic white subjects. 1,7,11 In accordance with the literature, our findings illustrate a high prevalence of comorbid atopic diseases and sensitizations to food and environmental allergens in both children and adults. However, we found that children had a significantly higher rate of asthma and positive patch test to foods compared with adults.…”
Section: Discussionsupporting
confidence: 78%
“…6,7,10 EoE occurs in most racial and ethnic groups, but through observational studies EoE appears to disproportionally affect non-Hispanic white subjects with an increased male-to-female ratio. 1,7,11 Patients with EoE often have a concurrent or history of atopic diseases as well as a family history of atopy. Atopic diseases such as food allergy, atopic dermatitis, allergic rhinitis, allergic conjunctivitis, and asthma have been reported in the majority of patients with EoE (50 -80%).…”
mentioning
confidence: 99%
“…The inflammatory response may cause bleeding, with blood in the vomit. Gastro-oesophageal reflux disease can occur as an adverse reaction to food, particularly in children, with or without development of eosinophilic oesophagitis (Moon and Kleinman, 1995;Ireland-Jenkin et al, 2008;Dalby et al, 2010).…”
Section: Vomiting and Gastro-oesophageal Reflux Diseasementioning
confidence: 99%
“…Other studies on retrospective review of upper endoscopy procedure or histopathology reports of children also describe increasing prevalence rates during the last years [11,12,13,14]. In a prospective evaluation of children and infants in Southern Denmark (pediatric population of 256,164; age: 0-16 years) with symptoms of gastroesophageal reflux disease during an 18-month period, 6 patients were diagnosed with EoE, corresponding to an annual incidence rate of 1.6 per 100,000 children [15]. A recent review summarizing 25 epidemiological studies concerning incidence and prevalence of EoE in children showed that the incidence of EoE varied depending on the geographic location from 0.7 to 10/100,000 per person-year and the prevalence ranged from 0.2 to 43/100,000 children and increased over time.…”
Section: Incidence and Prevalence Of Eoe Based On Endoscopy And Histomentioning
confidence: 99%